LEVERAGING ENTREPRENEURIAL ARTIFICIAL INTELLIGENCE TO ENHANCE URBAN AND REGIONAL DYNAMICS: A STUDY ON INNOVATION, ECONOMIC GROWTH, AND SMART CITY DEVELOPMENT IN ANAMBRA STATE NIGERIA - Iguocha Arinze Christian (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Growing rates of urbanization along with the emerging concept of smart cities intensified the dependence on the application of AI solutions for solving multifaceted urban issues. In the present research, a descriptive survey approach was used with an analytical focus to analyze the AI-based entrepreneurial activities and to identify the effects on innovation, smart cities and infrastructure. One hundred and twenty-four participants comprising technology professionals, new venture creators, and policymakers completed the study. Data were collected using the Entrepreneurial Artificial Intelligence Scale, validated through expert reviews, and with a reliability coefficient of 0.83. Participants were to rate AI’s impact using a 4 options Likert scale while data analysis included descriptive statistics, and ANOVA to compare the scores between occupations and different levels of education. Studies show that Entrepreneurial Artificial Intelligence (EAI) also contributes to improved process performance in managing cities as well as increases economic growth since it builds innovation platforms and generates new markets. In addition, AI-based smart city solutions enhance sustainability, efficiency and quality of life using intelligent construction of city infrastructures, big data and data-driven administration and citizen-centric services. By focusing on these research contributions and contributions of EAI as a whole, the study concludes by presenting policy implications for how policy-makers and urban planners could effectively utilize AI techniques for improving the regional development as well as achieving sustainable urbanism.